Testicular cancer follow-up costs in Germany from 2000 to 2015 - Michaeli, Christoph T.; Michaeli, Julia; Michaeli, Daniel (Journal of cancer research and clinical oncology, 2021)
Advances in testicular cancer screening and therapy increased 10-year survival to 97% despite a rising incidence; eventually expanding the population of survivors requiring follow-up. We analyzed 10-year follow-up costs after testicular cancer treatment in Germany during 2000, 2008, and 2015.
Gesehen am 25.01.2023